Compressive Behavior of Jacketed Specimens and Flexural Behavior of Concrete Beam Strengthened using Sodium Silicate Mortar - Maulana, Taufiq Ilham (International Journal of Integrated Engineering, 2019)
Damage in concrete structures depends on the load types. Flexural and axial loads are the most common load types that cause damages. The damage can be repaired by injecting materials such as sodium silicate. In this study, two methods are performed to repair concrete damages namely grouting in beam and jacketing on concrete cube samples with sodium silicate mortar. The grouting method was conducted in the first crack of beam, while the jacketing method was done by covering the concrete cube with sodium silicate mortar. The sample used was 15x15x15 cm3 of concrete cube and 15x15x60 cm3 of beam. The results showed that sodium silicate mortar improved 92% compared to the initial stage of compressive strength. However, the first crack at maximum load of the repaired beam occurred earlier than the controlled specimen. In general, the repairing method can be applied to reduce damage in concrete structures.